Concentration of Resources and Economic Growth - David Castells-Quintana (REGION, 2015)
In this letter I summarise the main results and contributions from my Ph.D. thesis on concentration of resources and economic development. The empirical analysis performed in the thesis, and summarised here, focuses on two mayor world trends in modern economic development, namely increasing agglomeration and rising inequalities within countries. In particular, the impact of both trends on long-run economic growth is studied, and results are discussed in light of relevant policy debate.
Keywords: 330; concentration; inequality; agglomeration; growth; development; Econometrics; Development Economics; Economic Growth; Urban Economics; World; countries; 1960-2010